Fixed Points for ψ-Graphic Contractions with Application to Integral Equations - N. Hussain; S. Al-Mezel; P. Salimi (Abstract and Applied Analysis)
The aim of this paper is to define modified weak α-ψ-contractive mappings and to establish fixed point results for such mappings defined on partial metric spaces using the notion of triangular α-admissibility. As an application, we prove new fixed point results for graphic weak ψ-contractive mappings. Moreover, some examples and an application to integral equation are given here to illustrate the usability of the obtained results.